2022
DOI: 10.1101/2021.12.30.21268532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Waning of SARS-CoV-2 Antibody levels response to inactivated cellular vaccine over 6 months among healthcare workers

Abstract: Background Health Care workers (HCW) are an important group affected by this pandemic and COVID-19 has presented substantial challenges for health professionals and health systems in many countries. The Brazilian vaccination plan implemented in October, so that third dose for HCW. However, the persistence of CoronaVac vaccine-induced immunity is unknown, and immunogenicity according to age cohorts may differ among individuals. Objective Evaluate the post vaccination immune humoral response and the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Even though this issue was beyond the scope of the current study, we found that the majority of recipients vaccinated with BNT162b2, Gam-COVID-Vac and ChAdOx1 nCoV-19 remained seropositive to SARS-CoV-2 virus at 6 months, in comparison to 40% of those vaccinated with BBIBP-CorV, with no significant differences regarding sex. A lower percentage of seropositivity at 6 months after vaccination with another inactivated SARS-CoV-2 vaccine (CoronaVac) was previously demonstrated in a similar study by Taminato et al, where only 20% of participants were seropositive for more than 6 months [ 36 ]. Of note, measuring just the Ab response against S protein, especially after being vaccinated with the whole-virus vaccines, such as BBIBP-CorV, might not be enough to evaluate the complete immune response, since the production of other Abs against different SARS-CoV-2 antigens is also induced [ 23 ].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Even though this issue was beyond the scope of the current study, we found that the majority of recipients vaccinated with BNT162b2, Gam-COVID-Vac and ChAdOx1 nCoV-19 remained seropositive to SARS-CoV-2 virus at 6 months, in comparison to 40% of those vaccinated with BBIBP-CorV, with no significant differences regarding sex. A lower percentage of seropositivity at 6 months after vaccination with another inactivated SARS-CoV-2 vaccine (CoronaVac) was previously demonstrated in a similar study by Taminato et al, where only 20% of participants were seropositive for more than 6 months [ 36 ]. Of note, measuring just the Ab response against S protein, especially after being vaccinated with the whole-virus vaccines, such as BBIBP-CorV, might not be enough to evaluate the complete immune response, since the production of other Abs against different SARS-CoV-2 antigens is also induced [ 23 ].…”
Section: Discussionmentioning
confidence: 74%
“…Thus, the assessment of post-vaccination titers/levels can help to better understand vaccine’s long-term efficacy and improve current vaccination strategies [ 34 ]. Indeed, serious concerns have been raised about the longevity of post-vaccination immunity, especially with the occurrence of new COVID-19 cases in countries where a high vaccination rate was reached [ 35 , 36 ]. In the longitudinal part of our study, we noticed a significant decline in Ab levels between two time points, at the 28th day and at 6 months, following the application of the second dose of BNT162b2, BBIBP-CorV, and Gam-COVID-Vac.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation